2002
DOI: 10.1210/endo.143.5.8813
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activity of Nuclei in Multinucleated Osteoclasts and Its Modulation by Calcitonin

Abstract: The function of osteoclasts is to digest the calcified bone matrix. Osteoclasts, together with myotubes, are among the rare examples of multinucleated cells found in higher vertebrates, resulting from the fusion of mononucleated progenitors belonging to the monocyte/macrophage lineage. So far, no information is available about function and transcriptional activity of multiple nuclei in osteoclasts. We have used a run-on technique to visualize RNA synthesis in individual nucleus. We provide the first evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…Interestingly, DAP12 was recently demonstrated to be one of three genes upregulated by the PU.1 transcription factor, which has previously been shown to be essential for osteoclast development. (28) Osteoclast function has been previously correlated with the degree of multinucleation (29) ; therefore, we were unable to determine if DAP12 plays a direct role in promoting the resorptive function of osteoclasts or whether it is the effect on development of multinuclear osteoclasts that indirectly affects the capacity for bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, DAP12 was recently demonstrated to be one of three genes upregulated by the PU.1 transcription factor, which has previously been shown to be essential for osteoclast development. (28) Osteoclast function has been previously correlated with the degree of multinucleation (29) ; therefore, we were unable to determine if DAP12 plays a direct role in promoting the resorptive function of osteoclasts or whether it is the effect on development of multinuclear osteoclasts that indirectly affects the capacity for bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, since the protein synthesis requirements are met through upregulated translation, increase in genome content through cell fusion is not required, and thus mTORC2 fraction decreases. It has been previously demonstrated that all osteoclast nuclei are similarly engaged in transcription, and that transcriptional activity of osteoclast nuclei is strongly upregulated when osteoclasts engage in resorption (Boissy et al, 2002). Our data suggest that genome content and transcriptional output are closely regulated during osteoclast formation as well as osteoclast function.…”
Section: Discussionmentioning
confidence: 99%
“…OCs are the only cells known to resorb bone, and OC resorptive capacity is thought to correlate with the number of OC nuclei present in bones. (18) To explore TREM2-DAP12-mediated regulation of OC resorption, we generated mature OCs using RANKL and M-CSF, and we subsequently examined the effect of TREM2 blockade on bone resorption. TREM2 mAb treatment inhibited resorption by OC in vitro.…”
Section: Figmentioning
confidence: 99%